THE NOTION OF BIG DATA AND ITS LEGAL ASPECTS - Sarvar Tojiboyev (International Journal of Business, Law and Political Science, 2025)
Objective:  The objective of this study is to highlight the rapid growth of data generated by society through the widespread use of the Internet and the need for new technologies to process large volumes of information. The paper examines how commercial organizations, especially giant companies with access to advanced technologies, have an advantage in data processing, while smaller organizations struggle to compete. Method: The paper reviews the IDC report, "The Data Age 2025," which outlines the trends in the information technology market until 2025. It emphasizes the projections regarding the growth in data volume, particularly the 60% of information expected to be produced by commercial organizations. Additionally, the paper discusses the application of Big Data technology, specifically in Amazon's automated system that uses customer data to personalize product offerings. Result: The study finds that by 2025, the total volume of data produced will reach 175 zettabytes, with a substantial portion of it generated by commercial entities. The increasing reliance on Big Data and automated systems will give companies with access to large-scale technologies a significant advantage. Organizations without access to these technologies may face challenges in competing due to their inability to process large amounts of data effectively. Novelty: The novelty of this paper lies in the exploration of the pressing need for advanced data processing technologies in today's data-driven society. It brings attention to the role of commercial companies, like Amazon, in utilizing Big Data to create personalized customer experiences, offering a glimpse into how data technologies are shaping future market dynamics and organizational strategies.